Severe lumbar radiculopathy with epidural venous plexus engorgement in a morbidly obese pediatric patient: A case report. Issue 33 (August 2019) - Jeong, Hee Joon; Sim, Woo Seog; Park, Hue Jung; Lee, Seung Hwan; Oh, Min Seok; Cho, Min Kyoung; Seon, Heui Jin; Lee, Jin Young
Abstract: Introduction: Engorgement of the epidural venous plexus (EVP) is a rare cause of nerve root impingement. Dilated epidural veins cause compression of the thecal sac and spinal nerve roots, leading to lumbar radiculopathy. Patient concerns: Here we describe a case of severe lumbar radiculopathy in a 15-year-old morbidly obese boy. Diagnosis: Enhanced lumbar magnetic resonance imaging revealed left sided L1–L2 disc protrusion and engorgement of the lumbar EVP, resulting in narrowing of the thecal sac in the entire lumbar spine. There was no evidence of an intra-abdominal mass, thrombosis of the inferior vena cava, or vascular malformation. Interventions: A caudal epidural block was administered under fluoroscopic guidance. The patient reported a 30% reduction in pain intensity for just 1 day. Outcomes: The patient has been followed up for 2 years. He continues to take medication, including morphine sulfate 15 mg, gabapentin 300 mg, and oxycodone 20 mg per day. He is on a diet with exercise for weight reduction. Conclusion: An engorged EVP should be considered in the differential diagnosis of radiculopathy in morbidly obese patients.